Validating Driver Behavior and Attitude Measure for Older Italian Drivers and Investigating Their Link to Rare Collision Events - Spano, Giuseppina; Caffò, Alessandro O.; Lopez, Antonella; Mallia, Luca; Gormley, Michael; Innamorati, Marco; Lucidi, Fabio; Bosco, Andrea (Frontiers in Psychology, 2019)
The present study aimed to: a) validate the factor structures of three scales assessing driving behaviour, attitudes towards traffic safety and self-regulation in driving, in a sample of Italian older adults, through Confirmatory Factor Analyses (CFAs) and, b) to determine the effectiveness of these measures in predicting the likelihood and the frequency of collision involvements in the following year. A 28-item Driver Behaviour Questionnaire (DBQ), a 16-item Attitudes Towards Traffic Safety (ATTS), a 21-item Extended Driving Mobility Questionnaire (DMQ-A) were administered to 369 active Italian drivers, aged between 60 and 91 years. Results showed a four-factor structure for the DBQ, a five-factor structure for the ATTS and a two-factor structure for the Extended DMQ-A, as the best fitting models. Hurdle model analysis of count data with extra-zeros showed that all factors of DBQ predicted the likelihood of road collisions. Risky behaviour, except for aggressive violations, self-regulation and attitudes towards traffic rules were associated with the frequency of collision involvement. The aforementioned three scales seemed to be a useful and concise suite of instruments assessing risky as well as protective factors of driving behaviour in elderly.